2022
DOI: 10.3390/ijerph192215342
|View full text |Cite
|
Sign up to set email alerts
|

Use of a mHealth System to Improve Antenatal Care in Low and Lower-Middle Income Countries: Report on Patients and Healthcare Workers’ Acceptability in Tanzania

Abstract: Antenatal care (ANC) is considered a cornerstone of reproductive health programmes, but many women face difficulties in accessing these services, particularly in some sub-Saharan African countries, such as Tanzania. This study aimed to test ANC visit acceptability using mHealth system PANDA (Pregnancy And Newborn Diagnostic Assessment) in the Mufindi district (Tanzania). We investigated the ANC visit acceptability of pregnant women and healthcare workers (HCWs) in an intervention area using the PANDA system co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…The DHIs were categorised into two primary groups according to their intended purpose: as a supplementary or substitute to routine care. Among the 61 included studies, 32 ( [77,71,72,23,69,54,55,33,34,36,37,40,92,41,42,43,44,88,45,46,47,70,49,50,51,58,79,57,56].…”
Section: Purpose Of Digital Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…The DHIs were categorised into two primary groups according to their intended purpose: as a supplementary or substitute to routine care. Among the 61 included studies, 32 ( [77,71,72,23,69,54,55,33,34,36,37,40,92,41,42,43,44,88,45,46,47,70,49,50,51,58,79,57,56].…”
Section: Purpose Of Digital Healthmentioning
confidence: 99%
“…Additionally, mobile phone apps are used as an interface to simplify data gathering, decision-making, and patient-HCP communication. A few of the included studies reported that the integration of mobile apps with telehealth services was used to augment healthcare quality [34,37,39,47,69,71,72].…”
Section: Purpose Of Digital Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the system was widely accepted by the majority of HCWs due to its ease of use. 31 Exploring user acceptability is thus crucial in implementing innovative mHealth technologies since it can give potential implementers valuable insight into factors influencing users’ motivation to utilize the technology. 30 According to Nilsen et al, one of the major challenges to the deployment and uptake of mHealth technology is user resistance, which can be related to both the technology and resistance to change.…”
Section: Introductionmentioning
confidence: 99%